HYDROGEN STORAGE IN TROPICAL CLIMATES: A REVIEW OF SAFE STORAGE METHODS FOR NIGERIA - Esieboma, Ogagaoghene; Oshodin, Ikponmwosa; Ibadin, Meshach; Osakwe, Daniel; Idele, Overcomer; Omorisiagbon, Abraham (Journal of Engineering & Technological Advances, 2025)
This review explores hydrogen storage methods with a focus on their suitability for Nigeria’s tropical climate, which presents unique environmental challenges such as high humidity, temperature fluctuations, and limited cold storage infrastructure. The objective of the study is to identify hydrogen storage solutions that are both technically viable and contextually appropriate for Nigeria, supporting the nation’s transition toward cleaner energy sources. The scope of the review encompasses both physical-based and material-based storage methods. A comparative evaluation was conducted using a structured, literature-based qualitative multi-criteria decision analysis framework that assessed each method based on safety, energy efficiency, cost-effectiveness, scalability, and long-term durability under tropical conditions. The findings reveal that while compressed gas remains the most established technology, it can pose risks under high ambient temperatures. Liquid hydrogen and cryo-compressed options were found to be energy-intensive and logistically challenging for tropical deployments. Among material-based methods, metal hydrides emerged as the most promising due to their thermal stability, compactness, and safer handling features. The study concludes that metal hydrides, particularly those tailored for moderate temperature operation, offer a strategic pathway for hydrogen storage in Nigeria. The review highlights the importance of local adaptation, calling for policies and research focused on climate-adapted technologies, integration with Nigeria’s renewable energy sources, and investment in infrastructure. These findings provide critical insights for stakeholders aiming to develop a sustainable hydrogen economy in tropical regions.